Linguistic Innovation through Blend Words in Jakarta Smart City Annual Report - Mulyajati, Enggar; Baroroh, Hilma Erfiani (Journal of Language and Literature Studies, 2025)
Blending is widely recognized as a creative and productive word formation process in Indonesian, commonly found in media, branding, and everyday communication. Despite its popularity in informal contexts, the use of blended words in formal government documents has not been thoroughly examined. This study explores the use of blending in the 2023 Jakarta Smart City (JSC) Annual Report, aiming to identify the types of blends and analyze their structural and semantic characteristics. Using a qualitative document analysis method and drawing on Mattiello’s framework, the research classifies blend words into three main categories: morphotactic, morphonological, and morphosemantic. The findings indicate that morphotactic blending, particularly total blends, is the most frequently occurring type. Moreover, the study reveals innovative blending patterns in Indonesian formal discourse, including the merging of blending with acronyms, as in Satpol PP and JakISPU, the adaptation of blends influenced by pronunciation, exemplified by Tije (from Trans Jakarta), and the integration of cross-linguistic elements such as TopEdu and JakTrack. These findings suggest that blending has expanded beyond its informal origins and now plays a significant role in shaping the language used in official and institutional communication. In addition, these patterns demonstrate how linguistic innovation functions as a tool for branding, accessibility, and modernization in bureaucratic language. By illustrating how blending enhances the clarity and appeal of government discourse, this study contributes to understanding the role of of morphological creativity in shaping inclusive, citizen-oriented, and digitally adaptive public communication in Indonesia.